The corrosion behavior and tensile strength of the 2060 Al-Li alloy with different heat treatments - Zheng, Xingwei; Yin, Haohao; Shu, Yan; Chu, Zhenhua; Liu, Zhiwei (Frontiers in Materials, 2022)
The structural safety and service life of civil aircraft can be decreased by corrosion damage to their aluminum components caused by long-term service in corrosive conditions. In this work, the effect of heat treatment on corrosion behavior and tensile strength was systematically analyzed for 2060 Al-Li alloy immersed in 3.5 wt.% NaCl solution for different corrosion times. The results show that the corrosion depths of the 2060-T4 and 2060-T6 Al-Li alloys immersed for 720 h are 85 μm and 93 μm, respectively. The ultimate tensile strengths of 2060-T4 and 2060-T6 Al-Li alloys immersed for 720 h were reduced by 5.8% and 6.4%, respectively. Linear relationships between tensile strength and the corrosion depths of 2060-T4 and 2060-T6 Al-Li alloys were established as σ_res=486-0.33h and σ_res=547-0.35h respectively.